2022
DOI: 10.3390/horticulturae8010043
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Zingiber officinale Roscoe (Ginger), Soil Properties and Soil Enzyme Activities Grown in Different Concentration of Mineral Fertilizers

Abstract: Ginger is rich in different chemical compounds such as phenolic compounds, terpenes, polysaccharides, lipids, organic acids, minerals, and vitamins. The present study investigated the effect of mineral fertilizers on the content of mineral elements in the rhizomes of Zingiber officinale Roscoe, soil enzymes activity, and soil properties in Surkhandarya Region, Uzbekistan. To the best of our knowledge, the present study is the first in Uzbekistan to investigate the mineral elements of ginger rhizome inhabiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Additionally, 6-shogaol–one increases the concentration of glutathione and activity of NAD(P)H: quinone oxidoreductase (NQO1) [ 18 ]. Other studies [ 19 , 20 , 21 ] showed that [ 6 ]-gingerol attenuates the induction of pro-inflammatory signal transduction, including the NF-kB, protein kinase-C and mitogen-activated protein kinases (MAPK) pathways in HaCaT cells.…”
Section: Pharmacological Properties Of Gingermentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, 6-shogaol–one increases the concentration of glutathione and activity of NAD(P)H: quinone oxidoreductase (NQO1) [ 18 ]. Other studies [ 19 , 20 , 21 ] showed that [ 6 ]-gingerol attenuates the induction of pro-inflammatory signal transduction, including the NF-kB, protein kinase-C and mitogen-activated protein kinases (MAPK) pathways in HaCaT cells.…”
Section: Pharmacological Properties Of Gingermentioning
confidence: 99%
“…Terpenes form approximately half to more than three percent of all compounds present in the rhizome. However, their composition in the plant may vary depending on the origin of the ginger [ 6 ]. The characteristic and specific aroma of ginger, regardless of the place of its occurrence and type, is mainly caused by sesquiterpene hydrocarbons, such as zingiberene (constituting about fifty percent of all the components) [ 7 ]), ar -curcumene, beta -bisabolene, alpha -farnesene and beta -sesquiphellandrene, as well as monoterpene hydrocarbons, such as citral ( cis and trans forms), linalool, geranial, limonene, camphene, alpha - and beta -pinene and alpha- and beta -phellandrene [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in fertility as a result of man made degradation of soils occurs as a result of damage to the amount and activity of microorganisms contained in it, deterioration in chemical and physical properties, which leads to a decrease in crop yields. [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis of existing literary sources, the most promising for our region is compost preparation -organic-mineral fertilizers from waste [10][11][12][13]. The demand for fruits and vegetables grown without the use of chemical fertilizers and pesticides among the population has sharply increased worldwide.…”
Section: Introductionmentioning
confidence: 99%